Identifying English as a foreign language students’ attitude to improving speaking skills through collaboration - Alzubi, Ali Abbas Falah; Nazim, Mohd; Ahmad, Jalal (Journal of Education and Learning (EduLearn), 2025)
Speaking skills, being an essential part of effective communication, are significant for English as a foreign language (EFL) students in today’s globalized world, and collaborative learning, being heterogeneous, assists them with more possibilities for enhancing and practicing the skills through a supportive environment, constructive feedback, and opportunities for real-world conversations. Therefore, this study aimed to identify EFL students’ attitudes toward enhancing speaking skills in a collaborative learning environment. The researchers, to achieve the study objective, used the descriptive survey method to collect the data from a sample of 360 participants in the Preparatory Year (PY) at Najran University. The study's instruments included a closed-ended questionnaire and a semi-structured interview. The results showed students having positive attitudes toward a collaborative learning environment can highly enhance their speaking skills. In addition, the respondents’ study level did not impact their responses to enhancing speaking skills in a collaborative learning environment; however, male students showed higher attitudes than their female counterparts. Finally, the interview analysis showed that students' speaking skills can be improved in a collaborative learning environment in many ways including a supportive environment, interesting activities, and technology use. Based on the findings, the study recommends incorporating collaborative learning strategies to strengthen other language skills.